2015
DOI: 10.3233/jpn-2012-0541
|View full text |Cite
|
Sign up to set email alerts
|

Impaired prefrontal cortical response by switching stimuli in autism spectrum disorders

Abstract: Working memory (WM) performance is considered to change according to the nature of the task by adequate and prompt activation of corresponding functional connectivity in the brain. In the present study, we examined continuous prefrontal hemodynamic changes depending on reciprocal disposition of WM and non-WM tasks using two-channel near-infrared spectroscopy. To investigate possible functional connectivity deficits in autism spectrum disorder (ASD) during these tasks, relative concentration changes in oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Nine fNIRS studies have investigated working memory and inhibition in ASD. These studies observed an atypical activation in the PFC during letter-fluency tasks (Iwanami et al, 2011(Iwanami et al, , 2010Kawakubo et al, 2009), working memory tasks (Narita, 2015;Yanagisawa et al, 2016) and task switching/inhibition (Funabiki et al, 2012a(Funabiki et al, , 2012bNarita et al, 2012).…”
Section: Working Memory and Inhibitionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nine fNIRS studies have investigated working memory and inhibition in ASD. These studies observed an atypical activation in the PFC during letter-fluency tasks (Iwanami et al, 2011(Iwanami et al, , 2010Kawakubo et al, 2009), working memory tasks (Narita, 2015;Yanagisawa et al, 2016) and task switching/inhibition (Funabiki et al, 2012a(Funabiki et al, , 2012bNarita et al, 2012).…”
Section: Working Memory and Inhibitionmentioning
confidence: 98%
“…Studies of working memory conversion showed that a switching tendency of hemodynamic activation in the PFC was obvious in TDC but was not shown instantly in ASD (Narita et al, 2012;Yanagisawa et al, 2016). Regarding inhibitory control ability in ASD, studies showed reduced activation in the right PFC during a Go/No-go task (Funabiki et al, 2012;Xiao et al, 2012) compared to a TDC group and in the left ventrolateral PFC during a stop signal task compared to an ADHD group (Ishii-Takahashi et al, 2014).…”
Section: Working Memory and Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation